Oral Candida colonization in HIV-infected patients in Londrina-PR, Brazil: antifungal susceptibility and virulence factors - de Paula, Suelen Balero; Morey, Alexandre Tadachi; Santos, Jussevania Pereira; dos Santos, Pollyanna M. C.; Gameiro, Danielle G.; Kerbauy, Gilselena; Sena, Ester M.; Ueda, Luiz T.; Carneiro, Marcelo; Pinge-Filho, Phileno; Yamauchi, Lucy Megumi; Yamada-Ogatta, Sueli Fumie (The Journal of Infection in Developing Countries, 2015)
Introduction: Host colonization by Candida species is an important predisposing factor to candidiasis, which seems to be more frequent in human immunodeficiency virus (HIV)-infected patients. Knowledge about the distribution, antifungal susceptibility, and virulence of oral Candida isolates is important for effective management of candidiasis. Methodology: Oral rinses were collected from 242 HIV-infected patients without clinical evidence of candidiasis seen at the AIDS referral center in Londrina, Brazil. Species were identified by standard phenotypic and molecular methods, and characterized in vitro according to antifungal susceptibility, cell surface hydrophobicity, biofilm formation, and enzyme activities. Results: Oral Candida colonization was detected in 50.4% of patients and combined use of antiretroviral therapy and protease inhibitor had a protective effect against colonization. Candida albicans (75.2%) was the most prevalent species. A high proportion of Candida spp. (39.9%) showed decreased susceptibility to fluconazole. Five isolates were resistant to nystatin. Protease and phospholipase activities were detected in 100% and 36.8% of isolates, respectively. Most isolates displayed a hydrophobic property that was associated with biofilm formation ability. Conclusions: A significant number of oral Candida species exhibiting decreased susceptibility to fluconazole were isolated from colonized HIV-infected individuals. Furthermore, all isolates expressed potential virulence attributes in vitro. Given the high incidence and severity of fungal infections in HIV-infected individuals, the results of this study reinforce the importance of antifungal susceptibility testing, which contributes to therapeutic strategies and highlights the need for continuous surveillance of Candida colonization in this population.